Estaquia e enxertia de garfagem em oliveira. - Ribeiro, Fabrício Carlotto (2010)
Brazil has a large consumer market for olive-derived products (Olea europaea L.); however, this new culture requires further technical investigation. Therefore, the determination of an efficient method of propagation is the first step in obtaining sufficient amount of plants for the establishment of a sustainable production system. Due to the lack of information surrounding the olive propagation, especially in Brazil, the present work aimed to improve the efficiency of the vegetative propagation by rooting of semi-hardwood cuttings and whip grafting. The trial was carried out at Embrapa Clima Temperado, Pelotas/RS, and it was divided into three experiments. The first one aimed to obtain information about performance of different substrates (Perlite, Vermiculite and Plantmax) to promote rooting of olive 'Frantoio'. It was evaluated the rooting of cuttings (%) and/or callus formation (%) and quality of rooting (root amount grown). The second experiment aimed to evaluate the rooting of semi-hardwood cutting of Olives 'Arbequina' and 'Arbosana' submitted to different sources and concentrations of auxin (0mg.L-1, IBA 2000mg.L-1, IBA 4000mg.L-1, NAA 250mg.L-1 and NAA 500mg.L-1). Also, it was evaluated the rooting of cuttings (%) and/or callus formation (%) and quality of rooting (root amount grown). The third batch assessed the behavior of different olive cultivars (Itrana, Tanche, Bosana, Barnea, Manzanilla, Seggianese, Canino, Picual, Taggiasca and Cipressino) grafted on privet. The measurements here were living grafts (%), shooting grafts (%), number of shoots and length of shoots (cm). It was verified that: in the first experiment the substrate associated with the use of IBA (2000mg.L-1), has no influence on the amount and quality of roots formed on semi-hardwood cuttings of olive 'Frantoio'. In the second experiment, olive cuttings of 'Arbequina' and 'Arbosana' reached up to 18.64% of rooting, indifferently of auxin source and concentration. Rooted cuttings of olive 'Arbequina' and 'Arbosana', untreated and treated with butyric acid (IBA) and naphthaleneacetic acid (NAA), showed low quality of rooting (around one to four main roots). In the third experiment, regarding whip grafting of olive grafts on privet tree, there are considerable variations among living grafts (grafts that remain green but without shooting), grafting set (grafts that show shoots and union between scion/rootstock), number and average length of shoots. The highest grafting set rates and number of shoots per olive graft on privet, occur after 120 days of grafting.